Optimizing surgical stabilization of rib fractures using intraoperative ultrasound localization. Issue 2 (August 2021) - Martin, Thomas J.; Cao, Jessica; Benoit, Eric; Kheirbek, Tareq
Abstract : BACKGROUND: Surgical stabilization of rib fractures (SSRF) significantly improve the outcomes of patients with rib fractures. Ultrasound is a specific modality for localizing rib fractures. We hypothesized that use of perioperative ultrasound localization of fracture sites optimizes surgical approach and clinical outcomes. METHODS: We performed a retrospective cohort study of adult patients undergoing SSRF and compared those with and without adjunctive perioperative ultrasound fracture localization. Our primary outcome was improved surgical efficiency as measured by incision length and total operative time. Secondary clinical outcomes included numeric pain score on follow-up visit and daily morphine milligram equivalent prescribed within 30 days from discharge. RESULTS: We performed 49 surgical rib fixations between 2015 and 2020; of which, 13 (26.5%) additionally underwent ultrasound localization (26.5%). There were no significant differences between groups in age, sex, number of ribs repaired, or days till surgery. More patients in the ultrasound group had nonflail chest wall injury (76.9% vs. 27.8%, p = 0.003). Use of perioperative ultrasound was associated with shorter incision length (median, 9 vs. 15.5 cm; p = 0.0001), shorter operative time (median, 120 vs. 174 minutes; p = 0.003), less daily morphine milligram equivalent (25 vs. 68 mg, p = 0.009), and reduced numeric pain score on follow up (median, 4 vs. 7, p = 0.05). CONCLUSION: Use of perioperative ultrasound localization of rib fractures to optimize surgical approach for SSRF was associated with reduced incision length, operative time, and opioid requirements on patient discharge. We recommend considering routine perioperative localization to improve surgical approach and efficiency during SSRF. LEVEL OF EVIDENCE: Therapeutic, level IV.